Seroprevalence of transfusion-transmissible infections among blood donors at National Blood Transfusion Service, Eritrea: a seven-year retrospective study - Nejat Siraj (BMC Infectious Diseases, 2018)
Abstract Background Blood transfusion is associated with several risks particularly exposure to blood transfusion-transmissible infections (TTI), including: Hepatitis B virus (HBV), Hepatitis C virus (HCV), Human immunodeficiency virus (HIV) and Syphilis, among others. The threat posed by these blood-borne pathogens is disproportionately high in Sub-Saharan Africa (SSA). This fact underscores the need for continuous surveillance of TTIs in the region. Therefore, the study objectives were to evaluate the prevalence of TTIs and donor characteristics associated with positivity for TTIs at the National Blood Transfusion Center (NBTC) in Asmara, Eritrea. Methods A retrospective analysis of blood donors’ records covering the period from January 2010 to December 2016 was undertaken. The records were analyzed to evaluate the annualised cumulative prevalence of TTIs. Chi-square test (χ2) or Fisher’s exact test was used to evaluate the relationship between serological positivity and particular donor characteristics. Logistic regression was fitted to identify factors associated with cumulative TTIs positivity. A P-value < 0.05 was considered statistically significant. Result A total of 60,236 consecutive blood donors were screened between 2010 and 2016. At least 3.6% of donated blood was positive for at least one TTI and 0.1% showed evidence of multiple infections. The sero-prevalence of HBV, HCV, HIV, syphilis and co-infection was 2.0, 0.7, 0.3 and 0.6%, respectively. Sex, type of donor and region were associated with TTI positivity. Except for donation frequency, there was a significant relationship (P < 0.005) between HBV, HCV, HIV and syphilis sero-positivity and other donor characteristics evaluated in the study. Conclusion The result demonstrates that Eritrea has relatively low TTI prevalence compared to other countries in Sub-Saharan Africa. However, the prevalence, particularly that of HCV, increased significantly in 2016. Enhancing donor screening and additional research utilizing nucleic acid based techniques should therefore be prioritized.